2023
DOI: 10.1002/pmic.202200437
|View full text |Cite
|
Sign up to set email alerts
|

Global profiling of lysine lactylation in human lungs

Ye‐Hong Yang,
Qiao‐Chu Wang,
Jie Kong
et al.

Abstract: Lactate is closely related to various cellular processes, such as angiogenesis, responses to hypoxia, and macrophage polarization, while regulating natural immune signaling pathways and promoting neurogenesis and cognitive function. Lysine lactylation (Kla) is a novel posttranslational modification, the examination of which may lead to new understanding of the nonmetabolic functions of lactate and the various physiological and pathological processes in which lactate is involved, such as infection, tumorigenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In contrast, lactylation motif analysis in HEK293T cells favored the amino acid residues K (−6, −1, +4, and +7), alanine (A) (+1, +2, +3, and +6), and G, 54 and motif analysis in healthy human lungs frequently identified isoleucine (I), glutamine (Q), and P residues. 55 However, these results did not reveal defined motifs or patterns. This indicates that profiles of the Kla sites are currently being collected.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast, lactylation motif analysis in HEK293T cells favored the amino acid residues K (−6, −1, +4, and +7), alanine (A) (+1, +2, +3, and +6), and G, 54 and motif analysis in healthy human lungs frequently identified isoleucine (I), glutamine (Q), and P residues. 55 However, these results did not reveal defined motifs or patterns. This indicates that profiles of the Kla sites are currently being collected.…”
Section: Discussionmentioning
confidence: 73%
“…The lactylation motif analysis revealed that K, G, and P were favored (Figure B). In contrast, lactylation motif analysis in HEK293T cells favored the amino acid residues K (−6, −1, +4, and +7), alanine (A) (+1, +2, +3, and +6), and G, and motif analysis in healthy human lungs frequently identified isoleucine (I), glutamine (Q), and P residues . However, these results did not reveal defined motifs or patterns.…”
Section: Discussionmentioning
confidence: 77%
“…To define the possible Kla motifs in lactylated proteins, the characteristic sequences of modified sites and their enrichment statistics were obtained by MoMo [28], and the following conservative patterns around lactylated peptides were obtained: xxxxxxAxxx_K_xxxxxxxxxx, xxxxxxVxxx_K_xxxxxxxxxx, and xxxxxxxxxA_K_xxxxxxxxxx (where x indicates a random amino acid residue) (Figure 1E). These motifs differ from those identified in human gastric cancer cells [20] and human lungs [21]. Heatmaps were created for the amino acid sequences surrounding lactylation sites; red indicates high frequency, and green indicates low frequency (Figure 1F).…”
Section: Analysis Of Lactylated Site Patternsmentioning
confidence: 93%
“…gastric cancer cells [20], human lungs [21], etc. However, the function of lactylation in one whole organism has not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation